Deskripsi Peristiwa Faktual dan Fiksional serta Keberterimaan Masyarakat Sekitar Terhadap Folklor Mbah Sodong di Kecamatan Karangtengah, Kabupaten Cianjur - Henri Henriyan Al Gadri (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2016)
This research is motivated by the desire to document and introduce folklore Mbah Sodong to the public. Besides, factual and fictional events of folklore Mbah Sodong have to be known because the character of folklore which is spread by word of mouth can result different stories or events in the folklore. Folklore Mbah Sodong has values of character education which benefit for people and education. From charcter education which is in folklore, it can be developed attitude, knowledge, and skill aspects. Moreover, causing human person wise and virtuous. Therefore, folklore Mbah Sodong is able to be a lesson at school in supporting nation character education to reach a goal of national education generally.